Autologous Nanofat Injection Combined with Fractional CO2 Laser in the Treatment of Atrophic Acne Scars - Rageh MA; Ibrahim SMA; Abdallah N; Tawfik AA (Dove Medical Press, 2024)
Mahmoud A Rageh,1 Shady Mahmoud Attia Ibrahim,1 Noha Abdallah,2 Abeer Attia Tawfik2 1Department of Dermatology, Faculty of Medicine, Al-Azhar University, Cairo, Egypt; 2Department of Medical Applications of Laser, National Institute of Laser Enhanced Sciences, Cairo University, Giza, EgyptCorrespondence: Mahmoud A Rageh, Department of Dermatology, Faculty of Medicine, Al-Azhar University, Al-Darrasah, Cairo, 11633, Egypt, Email dr.mahmoudrageh@gmail.comBackground: Atrophic acne scarring is a widely prevalent condition and one of the most distressing complications of acne vulgaris. Numerous options with variable outcomes are available for the treatment of acne scarring. Laser is considered a first‐line therapy for acne scars, and recently there has been a growing interest in using stem cells and their derivatives for treating acne scars. In addition, combined therapeutic modalities often achieve more satisfactory results than a single treatment.Objective: We tried to evaluate the role of nanofat and fractional CO2 laser as a combined treatment approach for atrophic acne scarring.Methods: Twenty-five patients with atrophic acne scarring were enrolled. They received a single session of intradermal nanofat injection, at different points 1 cm apart, for acne scars. Two weeks later, they were treated with three sessions of fractional CO2 laser at monthly intervals. Patients were evaluated three months after the last session using the quantitative Goodman and Baron scoring system. Pain, side effects, and patients' satisfaction were also evaluated.Results: There were two males and 23 females with a mean age of 25.96 years. Their skin type ranged between Fitzpatrick skin type III, IV, and V. Boxcar scars were the most common scar type in 13 patients (52%). After treatment, there was a significant reduction (p < 0.05) in the quantitative Goodman and Baron scores. The improvement was more evident in rolling scars. Seven patients reported significant improvement, and 12 reported marked improvement.Conclusion: This study showed that combining nanofat and fractional CO2 laser is a safe and effective treatment modality for atrophic acne scars.Keywords: acne scars, fractional laser, fat grafting, nanofat